Length–weight relationships for 13 fish species in the Tangwang River, a tributary of Songhua River, China. (2nd April 2018) - Wang, J. L.; Liu, W.; Ying, Ch.; Wang, F.; Li, P. L.; Wang, Ch.; Tang, F. J.
Summary: The present work provides length–weight relationships (LWRs) for 13 fish species belonging to six families. The fishes were collected with gill nets (mesh sizes 10, 20, 40, 60, 90, 120 mm) and set nets (5, 8, 10 mm mesh sizes) from April 2012 to September 2015.